A fire-resistant and heat-insulating polyurethane microporous rubber and its preparation method and application
By adding nickel aluminum phosphate to polyurethane microporous rubber, the defects of existing fire-resistant insulation materials in flame retardant performance and structural stability are solved, and efficient fire-resistant insulation effect is achieved, and is suitable for high-temperature environments such as power batteries of new energy vehicles.
Patent Information
- Application Number
- CN202411612751.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing fire-resistant thermal insulation materials have defects in flame retardant performance, structural stability and fragility, and cannot effectively prevent heat spread and penetration of high-temperature flames.
A refractory and heat-insulated polyurethane microporous rubber is used, which adds nickel aluminum phosphate to the rubber component. By forming a three-dimensional mesh structure when heated and catalyzedly decomposes free radicals, the flame retardant performance and ceramicized structure strength are enhanced.
It achieves efficient flame retardant and heat insulation performance, avoids the loose structure and fragility of the expansion flame retardant system, and has the characteristics of non-expanded ceramic fire-proof and heat insulation, and is suitable for new energy vehicle power batteries and other high-temperature environments.
Smart Images

Figure CN119119409B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fireproof and heat-insulating materials, and in particular to a fire-resistant and heat-insulating polyurethane microporous rubber and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have gradually become the main power batteries for new energy vehicles due to their high energy density, no memory effect and long cycle times. Among them, lithium iron phosphate batteries and ternary lithium batteries have become the mainstream, but their own stability is low and the risk of thermal runaway is relatively high.
[0003] Once a lithium-ion battery triggers thermal runaway, the temperature of the battery cell will rise sharply, leading to accidents such as excessive pressure, shell rupture, spontaneous combustion and even explosion. In addition, the spontaneous combustion of lithium-ion batteries has the characteristics of fast burning speed and difficulty in extinguishing. The flame temperature of thermal runaway of high-nickel ternary system can reach or even exceed 1200℃, at which temperature the aluminum plate can be quickly melted or the coating on the surface of the battery pack can be ignited. It is particularly important to prevent the heat from spreading after thermal runaway occurs and to prevent the flame of thousands of degrees Celsius from burning through the upper cover after the heat spreads.
[0004] The prevention and control methods of heat spread are mainly divided into active prevention and control and passive prevention and control. Active prevention and control mainly refers to reducing the risk of heat spread by means of active cooling; passive prevention and control mainly uses thermal insulation materials to block the spread of heat to the surrounding battery cells, thereby inhibiting the occurrence of heat spread. At present, the fireproof and heat-insulating materials used for passive prevention and control of battery packs mainly include flame-retardant foam, mica board, aerogel, ceramic silicone rubber and fire-retardant coatings.
[0005] The mainstream insulation materials currently used in the market all have certain defects, such as poor flame retardant and thermal insulation performance of flame retardant foams (PU, PE, EVA, etc.), brittle and easy to crack mica board structure, high cost of aerogel, high density of ceramic silicone rubber and easy to break during the ceramic process, high requirements for construction technology of fire retardant coatings, etc. In addition, the volume of the expansion flame retardant system increases several times or even dozens of times during the flame retardant process, resulting in a loose structure, which is not conducive to protecting the module that has not caught fire; ordinary ceramic polyurethane foam is prone to dripping after being heated and melted to bond inorganic powders and polymer residues, which is not conducive to the improvement of flame retardant grade and ceramic strength.
[0006] In addition, with the further improvement of the fire protection requirements in GB 38031-2020 "Safety Requirements for Power Batteries for Electric Vehicles", a non-expanding flame-retardant, heat-insulating, and high-temperature resistant material is needed for use in the field of fire protection and heat insulation. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a fire-resistant and heat-insulating polyurethane microporous rubber and its preparation method and application. By adding nickel aluminum phosphate to the rubber component, the problems of poor flame retardant performance, loose structure and easy breakage during combustion and inability to continuously flame retardant and heat-insulating existing flame-retardant polyurethane materials can be fundamentally avoided. The rubber can be applied to new energy vehicle power batteries, automotive interior and exterior decoration, precision equipment and instruments and other fields.
[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0009] One of the purposes of the present invention is to provide a fire-resistant and heat-insulating polyurethane microporous rubber, which is prepared from component A and component B in a weight ratio of 100: (45-55);
[0010] The A component includes the following components in weight percentage:
[0011] Polyether polyol 25~40%
[0012] Polyester polyol 5~10%
[0013] Ceramic powder 8~18%
[0014] Nickel aluminum phosphate 15~25%
[0015] Flame retardant 12~31%
[0016] Foaming agent 1.5~8.5%
[0017] Foam stabilizer 0.5~1.5%
[0018] Catalyst 0.05~0.2%;
[0019] The B component is polymethylene polyphenyl polyisocyanate.
[0020] The second purpose of the present invention is to provide a method for preparing the fire-resistant and heat-insulating polyurethane microporous rubber, wherein component A and component B are fully mixed in proportion and poured into a mold, aged, and demolded to obtain the fire-resistant and heat-insulating polyurethane microporous rubber.
[0021] The third object of the present invention is to provide the application of the fire-resistant and heat-insulating polyurethane microporous rubber in new energy vehicle power batteries, automotive interior and exterior decoration, and precision equipment and instruments.
[0022] The beneficial effects of the present invention are:
[0023] (1) In the present invention, nickel aluminum phosphate has good "adhesion" properties because its phosphate ions continuously undergo dehydration and condensation after being heated, and finally form a three-dimensional network structure connected by POP bonds. The solid phase substances such as residual carbon produced during heating and combustion have good "adhesion" properties, avoiding the decrease in flame retardancy and ceramic properties caused by the heated dripping of low-melting-point glass powder, which is easy to occur when using low-melting-point glass powder, and is beneficial to the improvement and stabilization of the flame retardancy level and ceramic structure strength of polyurethane microporous rubber. On the other hand, since nickel ions can capture and catalytically decompose free radicals produced by combustion during the flame retardant process, they play a role in gas phase flame retardancy, further improving the flame retardant efficiency of the system, and their electrostatic field strength is less than that of aluminum ions, making the entire nickel aluminum phosphate system more stable and easy to store and use.
[0024] (2) The non-expanding ceramic flame retardant solution used in the present invention fundamentally avoids the limitations of conventional flame retardant polyurethane materials, which are mostly expandable flame retardant systems, namely, the problems of poor flame retardant performance, loose structure during combustion, easy breakage and inability to continuously flame retardant and heat-insulating. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 FT-IR spectra of nickel aluminum phosphate, aluminum hydroxide, aluminum phosphate, and nickel hypophosphite hexahydrate prepared in Example 1. DETAILED DESCRIPTION
[0026] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0027] The present invention provides a fire-resistant and heat-insulating polyurethane microporous rubber, which is prepared from component A and component B in a weight ratio of 100:(45-55);
[0028] The A component includes the following components in weight percentage:
[0029] Polyether polyol 25~40%
[0030] Polyester polyol 5~10%
[0031] Ceramic powder 8~18%
[0032] Nickel aluminum phosphate 15~25%
[0033] Flame retardant 12~31%
[0034] Foaming agent 1.5~8.5%
[0035] Foam stabilizer 0.5~1.5%
[0036] Catalyst 0.05~0.2%;
[0037] The B component is polymethylene polyphenyl polyisocyanate.
[0038] Further, the polyether polyol is composed of three polyether polyols whose initiators are sorbitol, glycerol and propylene glycol respectively. Preferably, the polyether polyol is composed of sorbitol starting polyether polyol, glycerol starting polyether polyol and propylene glycol starting polyether polyol in a weight ratio of 1: (0.8~1.2): (2.5~3.5), with an average functionality of 2.7~3.7 and an average hydroxyl value of 150~300mg KOH / g. The polyether polyol has low viscosity, molecular chain flexibility, hydrolysis resistance, good low temperature toughness and process adaptability, and is used as the soft segment part in the polyurethane main chain.
[0039] Furthermore, the polyester polyol is an aromatic polyester polyol synthesized from phthalic anhydride and diethylene glycol, and has low viscosity, high aromatic content, high hydroxyl value, hydrolysis resistance and thermal stability.
[0040] Furthermore, the ceramic powder includes but is not limited to one or more of mica, kaolin, feldspar powder, talc, wollastonite powder, diatomaceous earth, clay mineral fillers, silicates, carbonates, phosphates, and metal hydroxides. Preferably, the average particle size (D50) is 5-20 μm.
[0041] Furthermore, in order to improve the uniformity of dispersion of the nickel aluminum phosphate in the polyurethane matrix, under preferred conditions, the average particle size (D50) of the nickel aluminum phosphate is 5-20 μm.
[0042] Further, the application scope of the polyurethane microporous rubber is expanded so that it can be used in power batteries, precision instruments and other application fields, and the flame retardant is a non-expansive flame retardant. Preferably, the flame retardant is a phosphorus flame retardant. More preferably, the flame retardant is 2-6% organic phosphorus flame retardant and 10-25% inorganic phosphorus flame retardant, calculated by weight percentage in component A. Among them, the organic phosphorus flame retardant includes but is not limited to one or more of dimethyl methylphosphonate (DMMP), diethyl ethylphosphonate (DEEP), triethyl phosphate (TEP), and resorcinol bis(diphenyl phosphate) (RDP); the inorganic phosphorus flame retardant includes but is not limited to one or more of type II ammonium polyphosphate, melamine resin-coated ammonium polyphosphate, silane resin-coated ammonium polyphosphate, epoxy resin-coated ammonium polyphosphate, ammonium hypophosphite, sodium hypophosphite, aluminum hypophosphite, magnesium hypophosphite, and calcium hypophosphite.
[0043] Furthermore, the blowing agent includes, but is not limited to, one or more of hydrofluorocarbons, fluorochloroolefins, n-pentane, isopentane and cyclopentane.
[0044] Furthermore, the foam stabilizer is a polysiloxane-oxyolefin block copolymer, which belongs to a class of surfactants and can promote nucleation and stabilize cell formation.
[0045] Further, the catalyst is an amine catalyst and / or an organic metal salt catalyst. Wherein, the organic metal salt catalyst includes but is not limited to one or more of an organic tin catalyst, an organic bismuth catalyst, an organic lead catalyst, and an organic antimony catalyst. Preferably, the catalyst is an amine catalyst and an organic tin catalyst in a weight ratio of 1: (0.9~1.1). Wherein, the amine catalyst includes but is not limited to one or more of bis(dimethylaminoethyl) ether and pentamethyldiethylenetriamine; the organic tin catalyst includes but is not limited to one or more of dibutyltin dilaurate and di(dodecylsulfide)dibutyltin.
[0046] In the present invention, the nickel aluminum phosphate is obtained by reacting phosphoric acid, an aluminum source and a nickel source.
[0047] Under preferred conditions, the aluminum source includes but is not limited to aluminum hydroxide; the nickel source includes but is not limited to nickel hypophosphite.
[0048] Further, the initial melting point of the nickel aluminum phosphate is 450-550°C, and the final melting point is 1200-1400°C. The initial melting point of the nickel aluminum phosphate can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or any value in the range of any two of the above values, and the final melting point of the nickel aluminum phosphate is 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or any value in the range of any two of the above values.
[0049] Furthermore, the phosphoric acid is dilute phosphoric acid, which is prepared by adding concentrated phosphoric acid to deionized water, and the mass ratio of concentrated phosphoric acid to deionized water is 1: (1-5), preferably 1: (1-3).
[0050] Furthermore, the molar ratio of the phosphoric acid to the aluminum source is 1: (0.5-1.5), calculated on the molar amount of phosphorus to aluminum; the molar ratio of the aluminum source to the nickel source is 10: (0.5-2), calculated on the molar amount of aluminum to nickel.
[0051] In order to avoid the material from reacting too quickly and causing the material in the system to agglomerate, under preferred conditions, the aluminum source and the nickel source are added in batches, and the aluminum source is first added in batches to the phosphoric acid for reaction and then the nickel source is added in batches for reaction.
[0052] The invention provides a method for preparing the fire-resistant heat-insulating polyurethane microporous rubber. The components A and B are fully mixed in proportion and poured into a mold, aged, and demolded to obtain the fire-resistant heat-insulating polyurethane microporous rubber.
[0053] Furthermore, the aging temperature is 25-65° C. and the time is 30-90 min.
[0054] Furthermore, the density of the fire-resistant and heat-insulating polyurethane microporous rubber is 0.10-0.35 g / cm 3 .
[0055] The present invention provides application of the fire-resistant and heat-insulating polyurethane microporous rubber in new energy vehicle power batteries, automobile interior and exterior decorations, and precision equipment and instruments.
[0056] Since the fire-resistant and heat-insulating polyurethane microporous rubber of the present invention has a small specific gravity, is non-expansive and flame-retardant, and has ceramicized fireproof and heat-insulating properties, it can be used in fire-resistant and heat-insulating applications for new energy vehicle power batteries, automotive interior and exterior trim, and precision equipment and instruments.
[0057] The technical solution of the present invention is described in detail below through specific embodiments.
[0058] In the following embodiments, the density is tested according to the method of GB / T 6343-2009; the flame retardant grade and the dripping test are tested according to the method of UL-94; the three-point bending strength is tested according to the method of GB / T 3810.4-2016; the thermal insulation performance test method is as follows: the polyurethane microporous rubber is coated on the electrophoretic steel plate and cured to a thickness of 4 mm, and then the polyurethane microporous rubber is continuously sprayed for 5 minutes using a butane spray gun with a flame temperature of 1200°C, during which the maximum temperature on the back of the electrophoretic steel plate is recorded using a contact K-type thermometer.
[0059] Example 1
[0060] 1. Preparation of nickel aluminum phosphate:
[0061] 85% phosphoric acid and deionized water were mixed in a mass ratio of 1:1.4 to obtain a phosphoric acid solution; aluminum hydroxide (n(P) : n(Al) = 1:1) was added to the 80°C phosphoric acid solution in portions under stirring for 1 hour, and then nickel hypophosphite hexahydrate (n(Al) : n(Ni) = 10:1) was added in portions for 1 hour to obtain a light green viscous liquid, the liquid was transferred to a glass dish, and placed in a 105°C oven to dry for 24 hours, taken out, and ground to obtain nickel aluminum phosphate with an average particle size (D50) of 12 μm, an initial melting point of 500°C, and a final melting point of 1300°C.
[0062] Figure 1This is a Fourier transform infrared spectra of the nickel aluminum phosphate, aluminum hydroxide, aluminum phosphate, and nickel hypophosphite hexahydrate prepared in Example 1. Figure 1 Medium, 501cm -1 is the bending vibration peak of Al-OP, 1100~1400cm -1 The broad absorption band is the stretching vibration peak of P=O, 780cm -1 is the symmetrical stretching vibration peak of Al-O, 520~670 cm -1 It is the stretching vibration peak of Ni-O. The infrared spectrum can show that nickel aluminum phosphate is synthesized in this embodiment.
[0063] 2. Preparation of fire-resistant and heat-insulating polyurethane microporous rubber:
[0064] The specific composition of component A is shown in Table 1. Among them, sorbitol starting polyether polyol was purchased from Hebei Yadong Chemical Group Co., Ltd., with an average functionality of 5.5 and a hydroxyl value of 490 mg KOH / g, hereinafter referred to as Yadong Polyether 1; glycerol starting polyether polyol was purchased from Hebei Yadong Chemical Group Co., Ltd., with an average functionality of 3 and a hydroxyl value of 34 mg KOH / g, hereinafter referred to as Yadong Polyether 2; propylene glycol starting polyether polyol was purchased from Hebei Yadong Chemical Group Co., Ltd., with an average functionality of 2 and a hydroxyl value of 110 mg KOH / g, hereinafter referred to as Yadong Polyether 3; polyester polyol was purchased from Stepan Chemical Co., Ltd., with an average functionality of 2.4 and a hydroxyl value of 315 mg KOH / g, hereinafter referred to as Stepan Polyester 1.
[0065] Component B was purchased from Wanhua polyphenyl polymethylene polyisocyanate with model number PM200.
[0066] Table 1
[0067]
[0068] In Table 1, the average functionality of Yadong polyether 1, polyether 2 and polyether 3 after mixing in proportion is 2.9, and the average hydroxyl value is 170.8 mg KOH / g.
[0069] Component A and component B were fully mixed in a weight ratio of 100:50, poured into a mold, aged in an oven at 30°C for 60 minutes, and demolded to obtain a polyurethane microporous rubber.
[0070] Examples 2-3 and Comparative Examples 1-2
[0071] The method of Example 1 is followed, except that the content of nickel aluminum phosphate in component A is adjusted, as shown in Table 2.
[0072] The performance of the polyurethane microporous rubbers prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested. The results are shown in Table 2.
[0073] Table 2
[0074]
[0075] It can be seen from Table 2 that with the increase of nickel aluminum phosphate content, the strength of polyurethane microporous rubber after porcelainization increases; however, when the amount of nickel aluminum phosphate reaches 30%, the polyurethane microporous rubber will drip when burning, and cracks will appear at the flame contact position during the spray test. The flame passes through the flame retardant layer, and the back temperature increases significantly, which leads to the risk of ignition, which is not conducive to the actual flame retardant effect.
[0076] Embodiment 4-5
[0077] The method of Example 1 is followed, except that the specific ingredients of component A are adjusted, and the amounts of each component are kept unchanged, as shown in Table 3.
[0078] Among them, Wanhua Polyether 1 is a sorbitol-initiated polyether polyol with an average functionality of 2 and a hydroxyl value of 112 mg KOH / g, purchased from Wanhua Chemical Group Co., Ltd.; Wanhua Polyether 2 is a sorbitol-initiated polyether polyol with an average functionality of 3 and a hydroxyl value of 35 mg KOH / g, purchased from Wanhua Chemical Group Co., Ltd.; Stepan Polyester 2 is a polyester polyol with an average functionality of 2 and a hydroxyl value of 315 mg KOH / g, purchased from Stepan Chemical Co., Ltd.
[0079] The performance of the polyurethane microporous rubber prepared in Examples 4-5 was tested, and the results are shown in Table 3.
[0080] Table 3
[0081]
[0082] It can be concluded from Table 3 that the flame retardant grade of the polyurethane microporous rubber prepared in Example 1 and Examples 4-5 is the highest V-0 grade, and after high-temperature calcination, it can form a ceramic protective layer with a certain strength, which plays a role in fire prevention and heat insulation.
[0083] Examples 6 to 9 and Comparative Examples 3 to 6
[0084] The method of Example 1 is followed, except that the molar ratio of P, Al and Ni in the preparation of nickel aluminum phosphate is adjusted, as shown in Table 4.
[0085] The performance of the polyurethane microporous rubbers prepared in Examples 6 to 9 and Comparative Examples 3 to 6 was tested. The results are shown in Table 4.
[0086] Table 4
[0087]
[0088] It can be seen from Table 4 that the molar ratio of P, Al and Ni in the preparation of nickel aluminum phosphate will affect the flame retardant, fire resistant and thermal insulation properties of polyurethane microporous rubber. When the molar ratio of P to Al is 1: (0.5~1.5) and the molar ratio of Al to Ni is 10: (0.5~2), the prepared nickel aluminum phosphate has the best effect on improving the flame retardant, fire resistant and thermal insulation properties of polyurethane microporous rubber.
[0089] Comparative Example 7
[0090] The method of Example 1 is followed, except that aluminum phosphate is used instead of nickel aluminum phosphate.
[0091] Comparative Example 8
[0092] The method of Example 1 is followed, except that low melting point glass powder is used instead of nickel aluminum phosphate.
[0093] Comparative Example 9
[0094] The method of Example 1 is followed, except that nickel aluminum phosphate is not used.
[0095] Comparative Example 10
[0096] The method of Example 1 is followed, except that a composition of aluminum phosphate and nickel hypophosphite hexahydrate is used instead of nickel aluminum phosphate, wherein the molar ratio of aluminum phosphate to nickel hypophosphite hexahydrate is 10:1 based on the molar amount of aluminum to nickel.
[0097] The performance of the polyurethane microporous rubber prepared in Comparative Examples 7 to 10 was tested, and the results are shown in Table 5.
[0098] Table 5
[0099]
[0100] From Table 5 we can see that:
[0101] Compared with Example 1, under the condition that the flame retardant composition and addition ratio remain unchanged, the use of aluminum phosphate (melting point of 1500°C) instead of nickel aluminum phosphate in Comparative Example 7 will reduce the flame retardant grade of the polyurethane microporous rubber from V-0 to V-1, and the thermal insulation performance will decrease.
[0102] Compared with Example 1, under the condition that the flame retardant composition and addition ratio remain unchanged, the use of low-melting-point glass powder in comparative example 8 instead of nickel aluminum phosphate will reduce the flame retardant grade of the polyurethane microporous rubber from V-0 to V-2, and the thermal insulation performance will be greatly reduced.
[0103] Compared with Example 1, the density of the polyurethane microporous rubber prepared in Comparative Example 9 without using nickel aluminum phosphate is increased, and the flame retardant grade is reduced from V-0 to HBF, with the worst flame retardant performance. Moreover, the structure is loose after high-temperature calcination, and it cannot play an effective role in fire prevention and heat insulation.
[0104] Compared with Example 1, under the condition that the flame retardant composition and addition ratio remain unchanged, the uniform dispersion effect of the composite of aluminum phosphate and nickel hypophosphite hexahydrate used in Comparative Example 10 in the polyurethane microporous rubber is poor, the flame retardant grade is reduced from V-0 to V-1, and the thermal insulation performance is also poor.
[0105] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A fire-resistant and heat-insulating polyurethane microporous rubber, characterized in that: It is prepared from component A and component B in a weight ratio of 100:(45-55); The A component includes the following components in weight percentage: Polyether polyol 25~40% Polyester polyol 5-10% Ceramic powder 8~18% Nickel aluminum phosphate 15~25% Flame retardant 12~31% Foaming agent 1.5~8.5% Foam stabilizer 0.5~1.5% Catalyst 0.05-0.2%; The B component is polymethylene polyphenyl polyisocyanate; The nickel aluminum phosphate is obtained by reacting phosphoric acid, an aluminum source and a nickel source, wherein the molar ratio of the phosphoric acid to the aluminum source is 1:(0.5-1.5), calculated on the molar amount of phosphorus to aluminum; the molar ratio of the aluminum source to the nickel source is 10:(0.5-2), calculated on the molar amount of aluminum to nickel.
2. The fire-resistant and heat-insulating polyurethane microporous rubber according to claim 1, characterized in that: The polyether polyol is composed of three polyether polyols whose initiators are sorbitol, glycerol and propylene glycol respectively; The polyester polyol is an aromatic polyester polyol synthesized from phthalic anhydride and diethylene glycol.
3. The fire-resistant and heat-insulating polyurethane microporous rubber according to claim 2, characterized in that: The polyether polyol is composed of sorbitol-started polyether polyol, glycerol-started polyether polyol and propylene glycol-started polyether polyol in a weight ratio of 1:(0.8-1.2):(2.5-3.5).
4. The fire-resistant and heat-insulating polyurethane microporous rubber according to claim 1, characterized in that: The ceramic powder is one or more of mica, kaolin, feldspar powder, talc, wollastonite powder, diatomaceous earth, silicate, carbonate, phosphate, and metal hydroxide; The flame retardant is a non-expanding flame retardant; The blowing agent is one or more of hydrofluorocarbons, chlorofluoroolefins, n-pentane, isopentane and cyclopentane; The foam stabilizer is a polysiloxane-olefin oxide block copolymer; The catalyst is an amine catalyst and / or an organic metal salt catalyst.
5. The fire-resistant and heat-insulating polyurethane microporous rubber according to claim 4, characterized in that: The flame retardant is a phosphorus-based flame retardant; The phosphorus flame retardant is an organic phosphorus flame retardant and / or an inorganic phosphorus flame retardant; The organophosphorus flame retardant is one or more of DMMP, DEEP, TEP, and RDP; The inorganic phosphorus flame retardant is one or more of type II ammonium polyphosphate, melamine resin coated ammonium polyphosphate, silane resin coated ammonium polyphosphate, epoxy resin coated ammonium polyphosphate, ammonium hypophosphite, sodium hypophosphite, aluminum hypophosphite, magnesium hypophosphite, and calcium hypophosphite; The catalyst is an amine catalyst and an organotin catalyst in a weight ratio of 1:(0.9-1.1); The amine catalyst is one or more of bis(dimethylaminoethyl) ether and pentamethyldiethylenetriamine; The organic tin catalyst is one or more of dibutyltin dilaurate and dibutyltin didodecylsulfide.
6. The fire-resistant and heat-insulating polyurethane microporous rubber according to claim 1, characterized in that: The initial melting point of the nickel aluminum phosphate is 450-550°C, and the final melting point is 1200-1400°C.
7. The method for preparing the fire-resistant and heat-insulating polyurethane microporous rubber according to any one of claims 1 to 6, characterized in that: The components A and B are fully mixed in proportion and poured into a mold, aged, and demoulded to obtain a fire-resistant and heat-insulating polyurethane microporous rubber.
8. The method for preparing the fire-resistant and heat-insulating polyurethane microporous rubber according to claim 7, characterized in that: The density of the fire-resistant and heat-insulating polyurethane microporous rubber is 0.10-0.35 g / cm 3 .
9. The method for preparing the fire-resistant and heat-insulating polyurethane microporous rubber according to claim 7, characterized in that: The aging temperature is 25-65° C. and the aging time is 30-90 minutes.
10. Use of the fire-resistant and heat-insulating polyurethane microporous rubber according to any one of claims 1 to 6 or the fire-resistant and heat-insulating polyurethane microporous rubber obtained by the preparation method according to any one of claims 7 to 9 in new energy vehicle power batteries, automotive interior and exterior decoration, and precision equipment and instruments.
Citation Information
Patent Citations
Intumescent flame retardant for mine
CN102558710A
Polyvinyl chloride modified polyphenylene oxide material for automobile plastic parts
CN103937203A